Identification of the UL56 protein of herpes simplex virus type 1 within the virion by immuno electron microscopy - Kehm, Roland; Gelderblom, Hans R.; Darai, Gholamreza (Virus genes, 1998)
Recently the UL56 protein of herpes simplex virus type 1 (HSV-1) was shown to be associated with the virion of HSV-1 as determined by Western blot analysis. The detection of the UL56 protein in infected cells and its association with virions of HSV-1 is of particular importance, pointing to a possible involvement of UL56 protein in virus-host interactions. In order to investigate the properties of the UL56 protein further immuno-localization was performed using rabbit hyperimmune serum against fusion recombinant UL56 protein and purified virions of HSV-1 strain F. The UL56 protein was detected in the HSV-1 virions by immuno gold negative staining.
Gesehen am 29.08.2024